RE-POTENSI POPULASI ENDEMIK DARI SPESIES KERANG PAHUT-PAHUT (Pharella acutidens) DI DAERAH KAWASAN KONSERVASI MANGROVE DAN BEKANTAN (KKMB) KOTA TARAKAN - Syam, Mulyadi; Luwu, Andi Putra; ., Halidin; ., Manahan; ., Erwin; Salim, Gazali (Jurnal Harpodon Borneo, 2013)
Kerang pahut - pahut (Pharella acutidens) has value economic from the protein content of 13.08 %. The research objective was to determine the amount of population density Pharella acutidens of KKMB in the Tarakan city. Knowing Morphometry of Pharella acutidens, the correlation between shell height with a weight of Pharella acutidens, the correlation between shell length with a weight of Pharella acutidens, the correlation between the thickness of the shell with a weight of Pharella acutidens. Knowing the environmental habitat of Pharella acutidens in terms of water quality (physical and chemical parameters). Methods of research used descriptive method. Techniques of data collection using survey research design in the field directly. Sampling techniques Pharella acutidens use the sampling area in KKMB with purposive sampling method. The results population density of Pharella acutidens at Station 1 is 0.0645+0.0375 ind/m and population density Pharella acutidens at Station 2 is 0.1234+0.0355 ind/m. Correlation between the length of the shell with weight of Pharella acutidens at Station 1 is 0.8, growth of allometri positive. Correlation between shell height with a weight is 0.7 , growth of allometri negative. Correlation between thick shells with a weight is 0.6 , growth of allometri negative. Correlation between shell length with a weight of meat in Station 2 is 0.6 with growth of allometri negative. Correlation between shell height meat weight is 0.3 with growth of allometri negative. Correlation between thick shells with meat weight is 0.4 with growth of allometri negative. Habitat of shells Pharella acutidens at Station 1 was salinity range 26.955+0.285 ppt ; DO range .29+0.21 ppm ; temperature range 28.355+0.2450 C ; pH range of 7.51+0.29 ; TDS range of 21.07+0.2 ppm. Habitat of shells Pharella acutidens at Station 2 is salinity range 27.155+0.195 ppt ; DO range 4.32+0.17 ppm ; temperature range 27.84+0.72 0C ; pH range of 7.41+0.17 ;TDS range of 21.09+0.27 ppm. Keywords : Population, Kerang Pahut, Pharella acutidens, KKMB, Tarakan City 2 2